Teahouse of the August Moon. - Sneider, Vern. (Signet, 1951)
A novel relating the problems of Captain Fisby, of the United States Military Team C-147, who is in charge of Plan B to improve the welfare of an Okinawan village. When the captain receives two geishas as a gift, Plan B is humorously altered.
13
Keywords: World War, 1939-1945 -- Fiction